A Preliminary Report on the Use of the Design of Experiments for the Production of a Synbiotic Yogurt Supplemented With Gluten FriendlyTM Flour and Bifidobacterium infantis - Bevilacqua, Antonio; Speranza, Barbara; Campaniello, Daniela; Sinigaglia, Milena; Corbo, Maria Rosaria; Lamacchia, Carmela (Frontiers in Microbiology, 2019)
The main goal of this paper was to design a synbiotic yogurt containing Bifidobacterium infantis and Gluten Friendly FlourTM; the proposed approach relies upon milk fermentation through the classical starter of yogurt (Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus) to avoid a strong production of acetic acid by bifidobacterial and inoculum of B. infantis after the fermentation. The research was divided in 3 steps. The aim of the first step was the optimization of fermentation kinetic by L. delbureckii and S. thermophilus, by combining the amount of flour (either Gluten Friendly Flour-GF- or Control Flour-CF) in milk, temperature and inoculum level; the factors were combined through a mixture design. As a result of this step, the best combination was pointed out: flour at 2.5 g/l; L. delbrueckii subsp. bulgaricus at 6 log cfu/ml; temperature at 37–40°C. The goal of the second step was to study the effect of flour (2.5 g/l) on the viability of B. infantis. GF prolonged the viability of the probiotic for 14 days. In the last step, a synbiotic yogurt, supplemented with GF and fermented with L. delbureckii and S. thermophilus, and then inoculated with B. infantis, was produced. The product was stored at 8 and 15°C. A positive effect of GF was found at 15°C, with B. infantis at 7.0 log cfu/g in GF sample and 5.5.5.7 log cfu/g in CF sample.